Human Development Index, Minimum Wage, Labor Force Participation Rate and Gross Regional Domestic Product on the Open Unemployment Rate in Banten Province - Mediansyah, Rizki; Hermanto, Bambang Agoes (Formosa Journal of Multidisciplinary Research, 2024)
This study aims to analyze how much factors affect the open unemployment rate in Banten Province. The analysis method used is panel data regression analysis, which combines time series data and cross-section data. The data used in this finding is secondary data obtained from BPS Banten Province during the period 2019 to 2023. The variables collected include human development index, minimum wage, employment and gross regional domestic product. Based on the panel data regression results, the best model obtained is CEM. The findings indicate that panel data regression analysis shows a significant effect of HDI, minimum wage, labor force participation rate, and GRDP on the open unemployment rate in Banten Province during the 2019-2023 period. The probability value below 0.05 corroborates this finding. An increase in minimum wage is positively correlated with an increase in open unemployment, while an increase in HDI, labor force participation rate, and GRDP are negatively correlated with open unemployment.